(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article examines the influence of social media on language use and personal identity formation among modern youth. Based on analysis of existing academic literature, the research illuminates the impact of social media platforms on linguistic changes and cultural identification.